2004
DOI: 10.1016/j.stam.2004.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Neutron capture nucleosynthesis in the universe

Abstract: First, the nucleosynthesis in the universe was reviewed. In particular, the neutron capture nucleosyntheses in the Big-Bang and the s-and r-processes were reviewed in detail. It was pointed out that keV-neutron capture cross sections were important for the study on the neutron capture nucleosynthesis. Second, our measurement of keV-neutron capture cross sections was explained briefly, and the results on 7 Li, 12 C, and 16 O were shown and compared with previous experimental values and the predicted values from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…Therefore, continuing the analysis of the radiative capture of neutrons by light atomic nuclei, which is part of the different thermonuclear cycles [17][18][19][20] and take part in one of the variants of reaction chains for inhomogeneous Big Bang models [21][22][23][24][25] this allow to the synthesis of heavy elements via the next chain of neutron capture reactions 1 H(n, γ) 2 H(n, γ) 3 H( 2 H, n) 4 He( 3 H, γ) 7 Li(n, γ) 8 Li( 4 He, n) 11 B(n, γ) 12 B(β − ) 12 C(n, γ) 13 C(n, γ) 14 C(n, γ) 15 …”
Section: Astrophysical Aspects Of the Reviewmentioning
confidence: 99%
“…Therefore, continuing the analysis of the radiative capture of neutrons by light atomic nuclei, which is part of the different thermonuclear cycles [17][18][19][20] and take part in one of the variants of reaction chains for inhomogeneous Big Bang models [21][22][23][24][25] this allow to the synthesis of heavy elements via the next chain of neutron capture reactions 1 H(n, γ) 2 H(n, γ) 3 H( 2 H, n) 4 He( 3 H, γ) 7 Li(n, γ) 8 Li( 4 He, n) 11 B(n, γ) 12 B(β − ) 12 C(n, γ) 13 C(n, γ) 14 C(n, γ) 15 …”
Section: Astrophysical Aspects Of the Reviewmentioning
confidence: 99%
“…For example, it is believed that the primordial nucleosynthesis followed the basic reaction chain of the form [6]: Furthermore, the reaction under consideration is the mirror reaction to the 7 Be(p, ) 8 B capture process, where 8 В decays into 8 Ве+e + + due to the weak interaction. Neutrinos from this reaction have rather high energy and have been registered on Earth over several decades, but the unstable 8 Ве nucleus decays into two -particles.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous work [24] for the n 6 Li system showed that it is possible to use the allowed scheme {42} for 6 Li without taking into account its forbidden configuration {6}. Therefore, we will further consider the second variant of the FS structure and potentials with the allowed scheme {43} for 7 Li as the main variant of the classification of FS and AS in such a system.…”
Section: Introductionmentioning
confidence: 99%
“…(31), because the 3 S 1 potential equals zero, completely determines the slope and location of the line in Fig. 7, shown the calculated cross section of the 3 Let us turn now to analysis of the total cross sections of 11 B(n, γ) 12 B reaction in the energy range 1-1000 keV and pay special attention to the signature of the resonances at 21 and 430 keV. In Fig.…”
Section: The Total Cross Section Of the Radiative Neutron Capture On mentioning
confidence: 99%
“…The study of the reaction 11 B(n, ) 12 B, from the astrophysical point of view, may play a definite role in reaction chains in the so-called inhomogeneous Big Bang models 1,2,3,4,5 that allow to the synthesis of heavy elements via the next chain of neutron capture reactions: 1 H(n,) 2 H(n,) 3 H( 2 Н,n) 4 He( 3 Н,) 7 Li(n,) 8 Li( 4 Не,n) 11 B(n,) 12 B( -) 12 C(n,) 13 C(n,) 14 С(n,) 15 C( -) 15 N(n,) 16 N( -) 16 О(n,) 17 О(n, 4 He) 14 C… (1) While, the study of the reaction 10 B(n, ) 11 B, from the astrophysical point of view, is not so interesting because this capture channel will be negligible, as opposed to 7 Li(, ) 11 B, for production of 11 B for reaction chains of Eq. (1).…”
Section: Astrophysical Aspects Of the Reviewmentioning
confidence: 99%